Extended release promethazine HCl using acrylic polymers by freeze-drying and spray-drying techniques: formulation considerations - Ruchi Tiwari; Birendra Srivastava; Gaurav Tiwari; Awanik Rai (Universidade de São Paulo, 2009)
The present study investigated a novel extended release system of promethazine hydrochloride (PHC) with acrylic polymers Eudragit RL100 and Eudragit S100 in different weight ratios (1:1 and 1: 5), and in combination (0.5+1.5), using freeze-drying and spray-drying techniques. Solid dispersions were characterized by Fourier-transformed infrared spectroscopy (FT-IR), differential scanning calorimetry (DSC), Powder X-ray diffractometry (PXRD), Nuclear magnetic resonance (NMR), Scanning electron microscopy (SEM), as well as solubility and in vitro dissolution studies in 0.1 N HCl (pH 1.2), double-distilled water and phosphate buffer (pH 7.4). Adsorption tests from drug solution to solid polymers were also performed. A selected solid dispersion system was developed into capsule dosage form and evaluated for in vitro dissolution studies. The progressive disappearance of drug peaks in thermotropic profiles of spray-dried dispersions were related to increasing amount of polymers, while SEM studies suggested homogenous dispersion of drug in polymer. Eudragit RL100 had a greater adsorptive capacity than Eudragit S100, and thus its combination in (0.5+1.5) for S100 and RL 100 exhibited a higher dissolution rate with 97.14% drug release for twelve hours. Among different formulations, capsules prepared by combination of acrylic polymers using spray-drying (1:0.5 + 1.5) displayed extended release of drug for twelve hours with 96.87% release followed by zero order kinetics (r²= 0.9986). O presente trabalho compreendeu estudo de um novo sistema de liberação prolongada de cloridrato de prometazina (PHC) com polímeros acrílicos Eudragit RL100 e Eudragit S100 em diferentes proporções em massa (1:1 e 1:5) e em combinação (0,5+1,5), utilizando técnicas de liofilização e de secagem por aspersão As dispersões sólidas foram caracterizadas por espectrofotometria no infravermelho por transformada de Fourier (FT-IR), calorimetria diferencial de varredura (DSC), difratometria de raios X (PXRD), Ressonância Magnética Nuclear (RMN), microscopia eletrônica de varredura (SEM) e, também, por estudos de solubilidade e de dissolução in vitro em HCl 0,1 N (pH 1,2), água bidestilada e tampão fosfato (pH 7,4). Realizaram-se, também, testes de adsorção da solução do fármaco nos polímeros sólidos. Desenvolveu-se sistema de dispersão sólida exclusiva dentro das cápsulas, que foi avaliado por meio de estudos de dissolução in vitro. Relacionou-se o desaparecimento progressivo de picos do fármaco em perfis termotrópicos de dispersões secas por spray à quantidade aumentada de polímero, enquanto os estudos de SEM sugeriram dispersão homogênea do fármaco no polímero. O Eudragit RL100 apresentou maior capacidade de adsorção do que o Eudragit S100 e, dessa forma, a combinação de (0,5+1,5) para S100 e para RL100 mostrou taxa de dissolução maior, com liberação de 94,17% de fármaco em 12 horas. Entre as várias formulações, as cápsulas preparadas pela combinação de polímeros acrílicos utilizando secagem por aspersão (0,5+1,5) apresentou liberação prolongada do fármaco em 12 horas, com 96,78% de liberação, seguindo cinética de ordem zero (r² = 0,9986)